Tanzania : A Handwashing Behavior Change Journey - World Bank (Washington, DC, 2012)
In Tanzania, nearly 30,000 people die annually due to diarrheal diseases and an estimated 12.6 percent of children suffer from diarrheal diseases. There is a widespread and deep-rooted belief that diarrhea is part of growing up and cannot be prevented. Working with the government and with non-governmental organizations, the Water and Sanitation Program (WSP) sought to increase rates of handwashing with soap among women and children, especially at critical junctures. This learning note documents the development of the project, with a focus on how it was designed, implemented, and monitored. Challenges and lessons learned are highlighted to assist program managers in designing and managing evidence-based handwashing with soap and other hygiene promotion programs.